2006
DOI: 10.1099/ijs.0.64034-0
|View full text |Cite
|
Sign up to set email alerts
|

Gordonia defluvii sp. nov., an actinomycete isolated from activated sludge foam

Abstract: Three strains of non-motile, Gram-positive, filamentous actinomycetes, isolates J4 T , J5 and J59, initially recognized microscopically in activated sludge foam by their distinctive branching patterns, were isolated by micromanipulation. The taxonomic positions of the isolates were determined using a polyphasic approach. Almost-complete 16S rRNA gene sequences of the isolates were aligned with corresponding sequences of representatives of the suborder Corynebacterineae and phylogenetic trees were inferred usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…In addition, some species of Fungus including Aspergillus, Mucor, Fusarium, and Penicilium are also petroleum degradation microorganism. Gordonia is widely distributed in land, coastal, and ocean environments, and could degrade various environmental pollutants, including benzothiophene, dibenzothiophene, alkanes, polycyclic aromatic hydrocarbons, and so on [54,67]. Different types of oil-degrading microorganisms are shown in Table 1.…”
Section: Species and Distribution Of Petroleum Degradation Microorganmentioning
confidence: 99%
“…In addition, some species of Fungus including Aspergillus, Mucor, Fusarium, and Penicilium are also petroleum degradation microorganism. Gordonia is widely distributed in land, coastal, and ocean environments, and could degrade various environmental pollutants, including benzothiophene, dibenzothiophene, alkanes, polycyclic aromatic hydrocarbons, and so on [54,67]. Different types of oil-degrading microorganisms are shown in Table 1.…”
Section: Species and Distribution Of Petroleum Degradation Microorganmentioning
confidence: 99%
“…Activated sludge samples from wastewater treatment plants with foaming issues normally contain multiple different filamentous organisms (Jenkins et al 2003). These filamentous organisms are generally bacteria, fungi, or algae whose cells do not become detached from each other after cell division and therefore grow in the form of filaments (Seviour and Nielsen 2010 et al 2003), and Millisia (Soddell et al 2006). Mycolic acid is a high molecular weight 3-hydroxy fatty acids with a long alkyl branch in the 2-postion, located on the cell wall of these organisms (Stratton et al 1998).…”
Section: Filamentous Organismsmentioning
confidence: 99%
“…In contrast to G. sihwensis DSM 44576 T , it is very interesting that strain Chol-3 T is a foam-producing bacterium when grown in rich media, a characteristic that is well-known for G. amarae (Iwahori et al, 2001;Pagilla et al, 2002;Carr et al, 2006) and that has also recently been found for Gordonia defluvii and other Gordonia species (Soddell et al, 2006;Shen et al, 2007). More differences between strain Chol-3 T and G. sihwensis can also be found in colony colour and form.…”
mentioning
confidence: 92%
“…Gordoniae appear to be widely distributed in nature and strains have been isolated from environments such as soil, wastewater, estuary sand, mangrove rhizosphere, oilproducing wells and activated sludge foam (Takeuchi & Hatano, 1998;Kummer et al, 1999;Kim et al, 2003;Maldonado et al, 2003;Xue et al, 2003;Shen et al, 2006;Soddell et al, 2006;Luo et al, 2007;Le Roes et al, 2008), as well as from clinical samples (Iida et al, 2005;Kageyama et al, 2006;Blaschke et al, 2007).…”
mentioning
confidence: 99%